Pathogenicity and Transcriptomic Analyses of Two “Candidatus Liberibacter asiaticus” Strains Harboring Different Types of Phages - Yongqin Zheng; Jingxue Zhang; Yun Li; Yaoxin Liu; Jiayin Liang; Cheng Wang; Fang Fang; Xiaoling Deng; Zheng Zheng (Microbiology Spectrum, 2023)
ABSTRACT “Candidatus Liberibacter asiaticus” is one of the putative causal agents of citrus Huanglongbing (HLB), a highly destructive disease threatening the global citrus industry. Several types of phages had been identified in “Ca. Liberibacter asiaticus” strains and found to affect the biology of “Ca. Liberibacter asiaticus.” However, little is known about the influence of phages in “Ca. Liberibacter asiaticus” pathogenicity. In this study, two “Ca. Liberibacter asiaticus” strains, PYN and PGD, harboring different types of phages were collected and used for pathogenicity analysis in periwinkle (Catharanthus roseus). Strain PYN carries a type 1 phage (P-YN-1), and PGD harbors a type 2 phage (P-GD-2). Compared to strain PYN, strain PGD exhibited a faster reproduction rate and higher virulence in periwinkle: leaf symptoms appeared earlier, and there was a stronger inhibition in the growth of new flush. Estimation of phage copy numbers by type-specific PCR indicated that there are multiple copies of phage P-YN-1 in strain PYN, while strain PGD carries only a single copy of phage P-GD-2. Genome-wide gene expression profiling revealed the lytic activity of P-YN-1 phage, as evidenced by the unique expression of genes involved in lytic cycle, which may limit the propagation of strain PYN and lead to a delayed infection in periwinkle. However, the activation of genes involved in lysogenic conversion of phage P-GD-1 indicated it could reside within the “Ca. Liberibacter asiaticus” genome as a prophage form in strain PGD. Comparative transcriptome analysis showed that the significant differences in expression of virulence factor genes, including genes associated with pathogenic effectors, transcriptional factors, the Znu transport system, and the heme biosynthesis pathway, could be another major determinant of virulence variation between two “Ca. Liberibacter asiaticus” strains. This study expanded our knowledge of “Ca. Liberibacter asiaticus” pathogenicity and provided new insights into the differences in pathogenicity between “Ca. Liberibacter asiaticus” strains. IMPORTANCE Citrus Huanglongbing (HLB), also called citrus greening disease, is a highly destructive disease threatening citrus production worldwide. “Candidatus Liberibacter asiaticus” is one of the most common putative causal agents of HLB. Phages of “Ca. Liberibacter asiaticus” have recently been identified and found to affect “Ca. Liberibacter asiaticus” biology. Here, we found that “Ca. Liberibacter asiaticus” strains harboring different types of phages (type 1 or type 2) showed different levels of pathogenicity and multiplication patterns in the periwinkle plant (Catharanthus roseus). Transcriptome analysis revealed the possible lytic activity of type 1 phage in a “Ca. Liberibacter asiaticus” strain, which could limit the propagation of “Ca. Liberibacter asiaticus” and lead to the delayed infection in periwinkle. The heterogeneity in the transcriptome profiles, particularly the significant differences in expression of virulence factors genes, could be another major determinant of difference in virulence observed between the two “Ca. Liberibacter asiaticus” strains. These findings improved our understanding of “Ca. Liberibacter asiaticus”-phage interaction and provided insight into “Ca. Liberibacter asiaticus” pathogenicity.